Interaksi Pembaca dan Narasi Interaktif dalam Sastra Digital: Kajian Resepsi pada Aplikasi Webnovel - Alpan Ahmadi; Wahidatul Murtafiah (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
The transformation of literature from print to digital platforms has altered the ontology of texts and the position of the reader. The Webnovel application introduces real-time interactivity features, such as paragraph-level comments and voting systems, allowing readers to participate directly in the storytelling process. This study aims to analyze the forms of reader interaction and how such interactivity influences narrative construction in digital literature through the lens of reception aesthetics. This study employs a qualitative approach with digital ethnography. Research data, consisting of reader comments and narrative fragments, were purposively sampled from popular ongoing works on the Webnovel app. Analysis was conducted by applying Wolfgang Iser's reception theory, specifically the concept of "indeterminacy" within the digital space. The findings indicate that reader reception on Webnovel is no longer private but rather performative and collective. Active readers fill narrative gaps instantaneously via comment sections, which in turn function as a "compass" for authors in determining plot direction, character consistency, and conflict resolution. This phenomenon marks a shift in narrative authority from a single author to a collaborative negotiation between the writer and the reader community. Interactivity on digital platforms has birthed a new aesthetic in literature, where the text becomes a fluid entity that is constantly evolving based on social dynamics in cyberspace.